Layer-by-layer solution-processed two-dimensional graphene oxide–polyethylenimine thin-film coatings for enhanced pool boiling heat transfer. (1st August 2023) - Lee, Jaemin; Kim, Jiheon; Seo, Byungseok; Shin, Dongjoon; Hwang, Sungho; Choi, Wonjoon
Abstract: Nanostructured surfaces are promising candidates for improving liquid-vapor phase-change heat transfer, and their simple fabrication can offer rapid screening of optimal surface characteristics where the phase change occurs. However, conventional fabrication techniques involve energy-intensive processes, such as high-temperature and vacuum conditions or harsh wet chemical treatments. Herein, we propose the use of Layer-by-Layer (LbL) solution-processed graphene oxide/polyethyleneimine (GO/PEI) coatings as ultrathin two-dimensional (2-D) functional surfaces on stainless-steel heaters to enhance the pool boiling heat transfer. The LbL deposition processes implementing repetitive contact and removal of positive and negatively charged water-based solutions directly fabricated GO/PEI bilayers on the heater surfaces. GO and PEI serve as the core plane-like 2-D nanostructure and the bonding agent, respectively, whereas the number of LbL cycles precisely adjusts the physicochemical properties. In the ultra-thin LbL coating thickness (< 85 nm), the significant enhancement rates of critical heat flux (∼ 125%) were obtained in comparison with the bare heater substrate when the working fluid was deionized water. The optimal LbL GO/PEI bilayers facilitate water molecule transport through the extended GO interlayer nanochannels and high-density pinholes, whereas the outer and inner surface characteristics, such as roughness, wettability, and thickness, manipulate liquid-vapor transition-detachment, as well as bubble dynamics. The simple yet effective LbL solution-processed coatings can pave the way for the development of diverse functional coatings of hybridized 2-D and polymeric materials for thermal energy management involving liquid-vapor phase-change heat transfer. Graphical Abstract: Image, graphical abstract